2009
DOI: 10.5539/ijbm.v4n12p129
|View full text |Cite
|
Sign up to set email alerts
|

Auditor Independence: Malaysian Accountant's Perception

Abstract: Independence is the primary justification of the existence, and thus the hallmark of the auditing profession. It is recognized as the primary attribute to be maintained by auditors in all circumstances. This study attempts to explore the determinants of auditor independence as perceived by Malaysian accountants using a self-administered mail survey. It was evidenced from the survey that size of audit fees is the most important factor, followed by competition, size of audit firm, tenure, provision of management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…As summarized by Schneider et al (2006), prior studies reached mixed results but most generally the results indicate that NAS can negatively affect auditor independence perception. This view has been reinforced recently by spectacular corporate collapses and apparent audit failures associated with them.This is in line with the suggestions in prior literature advocating the use of the elements of independence (e.g., Abu Bakar et al, 2005;Chen et al, 2005;and Abu Bakar & Ahmad, 2009). …”
Section: Provision Of Non-audit Services (Nas)supporting
confidence: 80%
See 1 more Smart Citation
“…As summarized by Schneider et al (2006), prior studies reached mixed results but most generally the results indicate that NAS can negatively affect auditor independence perception. This view has been reinforced recently by spectacular corporate collapses and apparent audit failures associated with them.This is in line with the suggestions in prior literature advocating the use of the elements of independence (e.g., Abu Bakar et al, 2005;Chen et al, 2005;and Abu Bakar & Ahmad, 2009). …”
Section: Provision Of Non-audit Services (Nas)supporting
confidence: 80%
“…8, No. 17;2013 too consider tenure of audit firms as an element of independence external auditing (Act SOX, 2002;George, 2004;Abu Bakar et al, 2005;Jackson et al, 2008;Abu Bakar & Ahmad, 2009). …”
Section: Auditor Tenurementioning
confidence: 99%
“…Previous research suggests a positive association between audit firm size with auditor independence (Abu Bakar, Abdul Rahman, & Abdul Rashid, 2005;Abu Bakar & Ahmad, 2009;DeAngelo, 1981;Gul, 1989;Shockley, 1981). It has been found that larger audit firms has higher auditor's independence as they are often considered to be more able to resist pressures from management compared to small audit firms.…”
Section: Audit Firm Sizementioning
confidence: 96%
“…However, as pointed out by (Goldman & Barlev, 1975), one should not conclude that large CPA firms are immune to pressures from their clients. The court cases which challenge the assumption that CPA firms acted independently indicate that a large CPA firm is no guarantee of its ability to resist pressures from clients, as the case with Arthur Andersen and Enron (Abu Bakar & Ahmad, 2009 (2009), mentioned that 91.4% of Malaysian audit firms fall into the category of small firms with one to two partners, while medium size audit firms with three to eight partners constitute 7.5% of the population of audit firms and the remaining figure of 1.1% are of the large size audit firms with more than nine partners. Salleh, et al (2008a) used three factors that are being used in the SMEs definitions to categorize the firm size.…”
Section: Audit Firm Sizementioning
confidence: 99%
See 1 more Smart Citation